Glutamate transporter contribution to retinal ganglion cell vulnerability in a rat model of multiple sclerosis - Boccuni, Isabella; Bas Orth, Carlos; Bruehl, Claus; Draguhn, Andreas; Fairless, Richard (Neurobiology of disease, 2023)
Glial glutamate transporters actively participate in neurotransmission and have a fundamental role in determining the ambient glutamate concentration in the extracellular space. Their expression is dynamically regulated in many diseases, including experimental autoimmune encephalomyelitis (EAE), a model of multiple sclerosis. In EAE, a downregulation has been reported which may render neurons more susceptible to glutamate excitotoxicity. In this study, we have investigated the expression of GLAST (EAAT1) and GLT-1 (EAAT2) in the retina of Brown Norway rats following induction of myelin oligodendrocyte glycoprotein (MOG)-EAE, which results in retinal ganglion cell (RGC) degeneration and dysfunction. In addition, we tested whether AAV-mediated overexpression of GLAST in the retina can protect RGCs from degeneration. To address the impact of glutamate transporter modulation on RGCs, we performed whole-cell recordings and measured tonic NMDA receptor-mediated currents in the absence and presence of a glutamate-uptake blocker. We report that αOFF-RGCs show larger tonic glutamate-induced currents than αON-RGCs, in line with their greater vulnerability under neuroinflammatory conditions. We further show that increased AAV-mediated expression of GLAST in the retina does indeed protect RGCs from degeneration during the inflammatory disease. Collectively, our study highlights the neuroprotective role of glutamate transporters in the EAE retina and provides a characterization of tonic glutamate-currents of αRGCs. The larger effects of increased extracellular glutamate concentration on the αOFF-subtype may underlie its enhanced vulnerability to degeneration.